Experimental Basis of the Bee Products Standard Substances Composition Safety for the Treatment of the Urogenital System - Shpychak, O. S. (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: The work presents the data of the literary sources review which suggests that nowadays, treatment of the urinary tract, including prostatitis and prostate adenoma, which are the most common and serious male disorders of and tend to increase their frequency, is the topical issue of the modern medicine. It is proved that the compounds of natural substances, standardized bee products in particular - honey powder (HP), propolis phenolic hydrophobic preparation (PPHP) and bee pollen (BP), are promising for the effective treatment of this disease. Materials and Methods: The results of studying the acute toxicity and safety of a new national medication of natural origin for treating the diseases of the genitourinary system, including prostatitis and prostate adenoma, which contains above named natural substances, are presented in the experimental part. Pharmacological, physiological, instrumental research methods and mathematical statistics methods have been used in the study. Results and Discussion: The analysis of morphological studies of testes and sperm functional state of rats demonstrates no change of morphological and functional indices in the experimental group compared with the control group. Basing on these studies, we can conclude that the mixture of active pharmaceutical ingredients (APIs) in the form of bee products standardized substances composition at a dose of 100 mg/kg demonstrates no toxic effects on spermatogenesis in male rats. The results of the study allergenic activity of the studied composition at the same dose indicate no hypersensitivity of immediate type reactions and no accumulation of homocytotrophic antibodies in the blood, and accordingly the no sensitizing activity, which was also confirmed by the â€œconjunctival testâ€ on guinea pigs. The research of the local irritating effect of the mixture of the APIs on the mucous membrane demonstrates the lack of such effect after a single application to the eye of rabbits. Conclusions: The study of the specific toxicity of the APIs mix in the form of a bee products standardized substances composition - HP, PPHP, and BP at a dose of 100 mg/kg, demonstrated no capacity to gonadotoxic and allergenic effect. It has been found that the formula of APIs has no effect on the secretory function and the state of the gastric mucosa and no irritating action at contacting with mucous membranes of an eye. The results of the studies of pharmacological activity and specific toxicity of the bee products standard substances composition - HP, PPHP, and BP â€“ allow to conclude that manufacturing such preparation is promising, and further preclinical researchers to obtain a permit to introduce a new preparation into clinical practice and industry are desirable.